H-Index Is Important for Postural Control for People with Impaired Foot Sole Sensation - Zhang, Shuqi (PLoS One, 2015)
INTRODUCTION: People with Peripheral Neuropathy (PN), especially those with impaired sensory inputs through the small-afferent fiber (type II afferent fibers) reflex loop (SAF), might depend more on the large-afferent fiber (type I afferent fibers) reflex loop (LAF) for postural control. PURPOSE: To examine whether the function of the LAF reflex loop, reflected by the H-reflex and ankle joint proprioception, influences postural control when the SAF reflex loop is impaired, as indicated by reduced foot sole cutaneous sensation. METHODS: Thirteen participants (8 women, 5 men) diagnosed with PN and 12 age-matched controls (7 women, 5 men) completed the testing protocol. Measures of interest included the H-index, active (AAP) and passive (PAP) ankle proprioception, plantar pressure sensitivity (PPS), average sway velocity (V(AVG)) and area (A(95)) during 30 seconds eyes-closed standing, 6-minute walk distance (6MWD) and timed up-and-go duration (TUG). RESULTS: Statistically significant group-dependent regression was observed between V(AVG) and H-index. Compared to the control group, the PN group demonstrated reduced PPS (2.0 ± 1.9 vs. 4.2 ± 1.2, P < .05) and H-index (63.6 ± 10.9 vs. 76.4 ± 16.0, P < .05), greater V(AVG) (3.5 ± 2.1 vs. 1.6 ± 0.6cm/s, P < .05) and A(95) (10.0 ± 10.1 vs. 2.5 ± 1.5cm(2), P < .05), shorter 6MWD (442.2 ± 93.0 vs. 525.3 ± 68.2m, P < .05), and longer TUG (9.4 ± 1.6 vs. 6.5 ± 1.3s, P < .05). Within the PN group, but not the control group, the H-index was correlated with V(AVG) (r = -.56, P < .05). Moreover, within the PN group only, PAP scores were correlated with 6MWD (r = -.68, P < .05) and TUG (r = -.59, P < .05) performance. No other statistically significant group difference, correlation or group-dependent regression was observed. CONCLUSION: V(AVG), 6MWD, and TUG correlated with LAF reflex loop function observed among those with impaired functioning of the SAF reflex loop. This observation suggests that the LAF reflex loop may be critical to the control of balance in those individuals suffering from small-fiber PN.